VISUAL-BASED AND VERBAL-BASED MATERIALS IN TEACHING WRITING TO STUDENTS WITH DIFFERENT LEARNING STYLES - Fiki Setiawan; Taiman Taiman (Gema Wiralodra, 2020)
This study was aimed to investigate the implementation of visual-based and verbal-based materials in teaching writing to students with different learning styles. This study employed a quasi-experimental design with a 2x2 factorial design conducted in the health analyst academy Indonesia. There were two experimental groups involved. Visual-based and verbal-based materials had been used as teaching media for collecting the data. The observation was also conducted to support the data findings. The research findings indicated that both visual-based and verbal-based materials were useful to be used in teaching writing to students with different learning styles. However, the findings indicated that visual-based material was more effective to be used in both spatial and linguistic learning styles students. The result of observation also showed that students considered visual-based material to be more interactive and exciting. Students' learning styles proved to have a significant influence on teaching materials, primarily when verbal-based material was implemented. The visual-based materials have a substantial impact on the students' writing ability. It could be concluded that visual-based material was adequate for the students with a spatial learning style, while verbal-based material was sufficient to the students with a linguistic learning style in teaching writing.